The Policy on the Granting of Permits for Change of Land Use (IPPT) in the Context of Transfer of Use of Agricultural Land to Equitable Residential Houses - Wahyu Murni Setyoningsih; Ana Silviana (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The increasing need for land caused by the community as a result of which there is a cultural shift in land use in Indonesia due to development demands. The purpose of this study is to find out and analyze the policy of granting Land Use Change Permits (IPPT) in the context of transferring the function of agricultural land use to residential houses in the Kendal regency area that is equitable. The approach method used in this study is an empirical juridical approach. The research specifications used are analytical descriptive research. The sources and types of data in this study are primary and secondary data through literature studies and field studies. The data were analyzed qualitatively using role theory and policy theory. The conclusion show in the Context of Transfer of Functions from the Use of Agricultural Land to Residential Houses in the Kendal Regency Areashows that land conversion is still happening and widespread due to several factors.